Three-Dimensional Semantics - Bochner, Gregory (Proceedings of Sinn und Bedeutung, 2019)
How can identity sentences involving distinct names be informative? Any theory of names facing the problem of informativity will need to appeal to descriptions. The crucial question is: at which level do descriptions play a role? Kripke showed that descriptions neither constitute nor fix the semantic contents of names. At the same time, his Millian views imply the problematic existence of modal illusions: some necessary truths are knowable only aposteriori even though there is no possible world in which they don’t hold. I sketch a new, metasemantic strategy that purports to avoid modal illusions within a referentialist framework: the relevant descriptions describe not extensions (descriptivism), not intensions (twodimensionalism), but names themselves (three-dimensionalism).